2012
DOI: 10.1101/gr.138248.112
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining replication origins in the face of genomic change

Abstract: Origins of replication present a paradox to evolutionary biologists. As a collection, they are absolutely essential genomic features, but individually are highly redundant and nonessential. It is therefore difficult to predict to what extent and in what regard origins are conserved over evolutionary time. Here, through a comparative genomic analysis of replication origins and chromosomal replication patterns in the budding yeasts Saccharomyces cerevisiae and Lachancea waltii, we assess to what extent replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 74 publications
6
59
0
Order By: Relevance
“…We see that all eight centromeres replicate early in S-phase (on average between 34 min for the earliest [Sakl0G] and 39 min for the latest [Sakl0F]), whereas telomeres tend to replicate later in S-phase (on average between 44 min [Sakl0E-right] and 51 min [Sakl0A-left]), as in S. cerevisiae (Raghuraman et al 2001), L. waltii (Di Rienzi et al 2012), and C. albicans (Koren et al 2010). The timing profile in figure 1 shows that for all chromosomes except Sakl0C-left, replication profiles alternate between large regions mostly replicated early and large regions mostly replicated late during S-phase as was already described in S. cerevisiae (McCune et al 2008), although a thorough mathematical analysis of similar data sets concluded that there is no evidence for clustering of origins with similar activation time in S. cerevisiae (Yang et al 2010).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We see that all eight centromeres replicate early in S-phase (on average between 34 min for the earliest [Sakl0G] and 39 min for the latest [Sakl0F]), whereas telomeres tend to replicate later in S-phase (on average between 44 min [Sakl0E-right] and 51 min [Sakl0A-left]), as in S. cerevisiae (Raghuraman et al 2001), L. waltii (Di Rienzi et al 2012), and C. albicans (Koren et al 2010). The timing profile in figure 1 shows that for all chromosomes except Sakl0C-left, replication profiles alternate between large regions mostly replicated early and large regions mostly replicated late during S-phase as was already described in S. cerevisiae (McCune et al 2008), although a thorough mathematical analysis of similar data sets concluded that there is no evidence for clustering of origins with similar activation time in S. cerevisiae (Yang et al 2010).…”
Section: Resultsmentioning
confidence: 95%
“…We compared the relative conservation of our set of 252 origins in L. kluyveri with the sets of 275 and 194 replication origins in S. cerevisiae and in L. waltii , respectively (Alvino et al 2007; Di Rienzi et al 2012). To achieve this goal, we computed all synteny regions between the genome of L. kluyveri and the two other genomes and determined whether origin-containing regions of 8 kb (4 kb on each side of the peak coordinates) in one genome was conserved in synteny and if an origin was also present in the corresponding region of conserved synteny in each of the two other genomes.…”
Section: Resultsmentioning
confidence: 99%
“…(a) Phylogenetic relationships and previously published ACS motifs are shown for S. cerevisiae (Broach et al 1983; Liachko et al 2013), L. waltii (Di Rienzi et al 2012), L. kluyveri (Liachko et al 2011), and K. lactis (Liachko et al 2010). (b) The sequences of the native (ARS) and optimized (OPT) panARS elements are shown.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…It was then proposed that ssDNA formation at replication origins during nucleotide shortage caused by the treatment with hydroxyurea (HU, an inhibitor of the ribonucleotide reductase) is an evolutionarily conserved process and can be exploited in order to map origins of replication in diverse organisms. Indeed, HU treatment has been used to identify origins of replication in diverse yeast species such as Schizosaccharomyces pombe [2], Lachancea waltii [4], and Saccharomyces bayanus (G. Alvino, M. Dunham, B. Brewer, and M.K.…”
Section: Introductionmentioning
confidence: 99%